Natural killer cell number and phenotype in bovine peripheral blood is influenced by age - Graham, Elizabeth M.; Thom, Michelle L.; Howard, Chris J.; Boysen, Preben; Storset, Anne K.; Sopp, Paul; Hope, Jayne C. (Veterinary immunology and immunopathology, 2009)
Natural killer (NK) cells are critical to the innate defence against intracellular infection. High NK cell frequencies have been detected in human neonates, which may compensate for the relative immaturity of the specific immune response. Additionally, phenotypic subsets of NK cells have been identified in humans with different functional properties. In this study, we examined the age distribution and phenotype of NK populations in bovine peripheral blood, including neonatal animals. We found that the NK cell populations defined by the phenotypes CD3 −CD2 + and NKp46 + largely overlapped, so that the majority of NK cells in bovine peripheral blood were CD3 −CD2 +NKp46 +. The remainder of the NK-like cells comprised two minor populations, CD3 −CD2 +NKp46 − and CD3 −CD2 −NKp46 +; the relative proportions of these varied with age. The lowest frequency of NK cells was recorded in 1-day-old calves, with the highest frequency in day 0 calves. The phenotypic characteristics of CD3 −CD2 + and NKp46 + NK populations were similar; both populations expressed CD45RO, CD45RB, CD11b, CC84, CD8αα and CD8αβ and did not express CD21, WC1, CD14 or γδ TCR. Age-related phenotypic differences were apparent. The phenotypic characteristics of three NK subpopulations were described; a significantly greater proportion of the CD3 −CD2 −NKp46 + population expressed CD8α compared to CD3 −CD2 +NKp46 + cells. Furthermore, a significantly greater proportion of the CD3 −CD2 +NKp46 − population expressed CD8 compared to total CD3 −CD2 + cells. Adult cattle had a significantly higher proportion of perforin + cells compared to calves aged ≤6 weeks. In this age group, the majority of perforin + cells expressed NKp46, while in adults the majority of perforin + cells were NKp46 −. However, the proportion of NKp46 + and CD3 −CD2 + cells that expressed perforin was not significantly different in any age group tested.